New insights in gastrointestinal “pediatric” neoplasms in adult patients: pancreatoblastoma, hepatoblastoma and embryonal sarcoma of the liver. A practical approach by GIPPI-GIPAD Groups - Tsvetkova, Vassilena; Magro, Gaetano; Broggi, Giuseppe; Luchini, Claudio; Cappello, Filippo; Caporalini, Chiara; Buccoliero, Anna Maria; Santoro, Luisa (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
Pediatric solid neoplasms are rare and very different from those observed in adults. The majority of them are referred to as embryonal because they arise as a result of alterations in the processes of organogenesis or normal growth and are characterized by proliferation of primitive cells, reproducing the corresponding tissue at various stages of embryonic development. This review will focus on embryonal gastrointestinal pediatric neoplasms in adult patients, including pancreatoblastoma, hepatoblastoma, and embryonal sarcoma of the liver. Although they are classically considered pediatric neoplasms, they may (rarely) occur in adult patients. Hepatoblastoma represents the most frequent liver neoplasm in the pediatric population, followed by hepatocellular carcinoma and embryonal sarcoma of the liver; while pancreatoblastoma is the most common malignant pancreatic tumor in childhood. Both in children and adults, the mainstay of treatment is complete surgical resection, either up front or following neoadjuvant chemotherapy. Unresectable and/or metastatic neoplasms may be amenable to complete delayed surgery after neoadjuvant chemotherapy. However, these neoplasms display a more aggressive behavior and overall poorer prognosis in adults than in children, probably because they are diagnosed in later stages of diseases.